1972
DOI: 10.1126/science.177.4047.426
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Cardiac Glycoside Content of Monarch Butterflies from Natural Populations in Eastern North America

Abstract: A new spectrophotometric assay has been used to determine the gross concentration of cardiac glycoside in individual monarch butterflies. Adults sampled during the fall migration in four areas of eastern North America exhibited a wide variation in cardiac glycoside concentration. The correlation between spectrophotometrically measured concentrations and emetic dose determinations supports the existence of a broad palatability spectrum in wild monarch butterflies. The cardiac gylcoside concentration is greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(90 citation statements)
references
References 8 publications
(1 reference statement)
2
88
0
Order By: Relevance
“…In contrast to these findings, laboratory studies using fifth instar larvae in bioassays found no effect of CG levels in diet, or different Asclepias species, on growth of IV and V instar larvae and fecundity of subsequent adults (Erickson 1973;Cohen 1983). Variation of adult size in the field in relation to CG concentration has been interpreted as indicating a physiological cost (Brower et al 1972), but this has been criticised on various grounds (Dixon et al 1978).…”
Section: Introductionmentioning
confidence: 93%
“…In contrast to these findings, laboratory studies using fifth instar larvae in bioassays found no effect of CG levels in diet, or different Asclepias species, on growth of IV and V instar larvae and fecundity of subsequent adults (Erickson 1973;Cohen 1983). Variation of adult size in the field in relation to CG concentration has been interpreted as indicating a physiological cost (Brower et al 1972), but this has been criticised on various grounds (Dixon et al 1978).…”
Section: Introductionmentioning
confidence: 93%
“…Individual plant and butterfly samples were prepared and extracted with 95 % ethanol as described by Brower et al (1972). Spectrophotometric determinations of cardenolide concentrations in the [1983][1984] samples were performed at 20 °C and 622 nm with alkaline 2,2'-,4,4'-tetranitrodiphenyl (TNDP) on a Perkin Elmer 559A spectrophotometer as described in Brower et al (1972, Brower & Moffitt (1974), Lynch & Martin (1987) and .…”
Section: Determination Of Total Cardenolide Contentmentioning
confidence: 99%
“…A recent study (3) has shown that monarch butterflies from natural populations exhibit palatability spectra and include individuals that are only moderately unpalatable. A predator might have to experience more than one of these before it was conditioned to avoid subsequent individuals.…”
mentioning
confidence: 99%